KEANEKARAGAMAN VEGETASI TEGAKAN PENYUSUN HUTAN TEMBAWANG DUSUN SEMONCOL KABUPATEN SANGGAU - Rizkiyah, Nur; Dewantara, Iswan; Herawatiningsih, Ratna (Universitas Tanjungpura, 2013)
The research was conducted in tembawang forest, Semoncol hamlet, Sanggau regency. The purpose of the research was to find out diversity of forest vegetation filling Tembawang forest and vegetation which dominate the forest. The research would benefit poeple to know composition of forest stands and to reserve the Tembawang forst According to analysis on vegetation, it was found that there were 21 variesties of forest stands,namely: Trees of Rubber, Rambutan, Pluntan, Durian bian, Durian, Jambu air mawar, Rambai, Langsat, Tengkawang tungkul, Leban, Kokosan, Asam kemantan, Duku, Cocoa, Petai, Plaik, Jengkol, Mangosteen, Melinjo, Nyatoh, and Cempedak. Meanwhile, based on analysis of data there were dominant trees which filled the forest based on INP seed broadcast, namely Rubber 63,9535%, Rambutan 23,2558%, and Pluntan 22,0930%. According to saplings type, it was represented by Rubber 150,5906%, Rambutan 22,9579%, Pluntan 16,6939%, Asam kemantan 10,7964%, Leban 10,5236%, Langsat 10,4498%. In trunk level it can be seen that Rubber was 153,8066%, Jambu air mawar was 24,4901%, and Cocoa was 19,7235%, From the there, it represented that Rubber was 180,6131% and Pluntan 15,9850%. From quantitative analysis it showed that dominant index value (C) there were no species dominating over other species or community structure was stable because C=0. Variety type ( ) was in moderate group ( 1 ? ? 3), abundant indek (e) was abundant because e = 1. Key words:Forests, Tembawang, Diversity,Vegetation, Semoncol